The average amount of precipitation in the area of the carinthiastatistical region during the period between 1961 and 2017 - Praprotnik, Aleš (Journal for Geography, 2021)
The average amount of precipitation in the area of the carinthiastatistical region during the period between 1961 and 2017 The article shows the annual precipitation in the Carinthia statistical region. We analysed the amount of precipitation of 18 meteorological stations in the referential period between the years 1961 and 2017. In the process we dealt with different meteorological variables; amount of precipitation, number of days with precipitation over 0,1 mm, and maximum daily precipitation.